2008
DOI: 10.1002/em.20440
|View full text |Cite
|
Sign up to set email alerts
|

Radiation‐induced bystander effects in vivo are epigenetically regulated in a tissue‐specific manner

Abstract: Exposure of animal body parts to ionizing radiation (IR) can lead to molecular changes in distant shielded “bystander” tissues and organs. Nevertheless, tissue specificity of bystander responses within the same organism has not been examined in detail. Studies on in vivo bystander effect conducted so far analyzed changes induced by single‐dose exposure. The potential of fractionated irradiation to induce bystander effects in vivo has never been studied. We analyzed changes in global DNA methylation and microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 60 publications
0
70
0
Order By: Relevance
“…Although fractionated irradiation was also applied in vivo to study the bystander effect on the level of DNA epigenetic changes in the non-exposed spleen of cranial irradiated mice (Ilnytskyy et al, 2009), the fraction doses used were far below those clinically applied. However, the authors observed that acute irradiation induced more pronounced bystander effect than fractionated irradiation.…”
Section: Fractionated Irradiation and Bystander Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Although fractionated irradiation was also applied in vivo to study the bystander effect on the level of DNA epigenetic changes in the non-exposed spleen of cranial irradiated mice (Ilnytskyy et al, 2009), the fraction doses used were far below those clinically applied. However, the authors observed that acute irradiation induced more pronounced bystander effect than fractionated irradiation.…”
Section: Fractionated Irradiation and Bystander Effectmentioning
confidence: 99%
“…The radiation-induced global genome DNA methylation changes were shown to be dose-dependent, sex-and tissue specific and long-persistant. Tissue specificity of bystander responses within the same organism has also been examined by Ilnytskyy et al (2009). They analyzed changes in global DNA methylation in spleen of mice whole-body or cranial exposed to single 0.5 Gy of X-rays or to the same dose given in five 0.1 Gy fractions.…”
Section: In Vivo Bystander Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings have also shown significant loss of global DNA methylation and a reduction of methyl-binding protein MeCP2 expression in both acutely radiation exposed and unexposed bystander spleen at 6 hr, 96 hr, and 14 days after irradiation [57]. This indicates that epigenetic effects might also be involved in the mechanism of the abscopal effect.…”
Section: Mechanisms Of the Abscopal Effectmentioning
confidence: 93%